PENGARUH PROFITABILITAS, TUNNELING INCENTIVE, MEKANISME BONUS, DAN INTANGIBLE ASET TERHADAP TRANSFER PRICING DENGAN TAX MINIMIZATION SEBAGAI VARIABEL MODERASI - Yaramah, Wati; Abbas, Dirvi Surya; Wibowo, Maharani Nur Restu; Setiawan, Miyah Maulidah; Lindeawati, Putri (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
The purpose of this study is to determine the effect of profitability, tunneling incentives, bonus mechanisms, and intangible assets on transfer pricing with taxnminimization as a moderating variable in Consumer Non-Cyclicals sub-sectormcompanies listed on the Indonesia Stock Exchange (IDX). The research time periodnused was 5 years, namely the period 2018 – 2022. The sampling technique used purposive sampling technique. Based on predetermined criteria obtained 9 companies. The type of data used is secondary data obtained from the IndonesianStock Exchange website. The analytical method used is panel data regression analysis. The results of the study show that the bonus and intangible asset mechanisms have an effect on transfer pricing. Tax minimization is able to moderate the effect of inventive tunneling on transfer pricing, but cannot moderate the effect of profitability, bonus mechanisms, and intangible assets. Profitability, bonus mechanisms and intangible assets together have an influence on transfer pricing.